PENGARUH MODEL PEMBELAJARAN TIPE JIGSAW DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA - M. Arifky Pratama (Madaris: Jurnal Guru Inovatif, 2022)
ABSTRACT This research aims to find out the The Effect of Applying Jigsaw Type Learning Model by Using Audio Visual Media to Learning Outcomes Students’. This type of research was experimental research, using the research design of Non-Randomized Control-Group Pretest-Posttest Design. The sample of this research was 40 students divided into 2 groups namely the experimental group and the control group. The data analysis techniques used to test the hypothesis in this research using the t-test. The results showed that there is an effect of interest and learning outcomes on the material Environmental Pollution between the Jigsaw model by using audio visual media and Conventional Learning. The result of research of experiment class students is higher than control class, the mean value of student's learning result in the experimental class is 78,70 while in the control class is 72,41. After that the t-test obtained the value of 0.000 statistical value is less than 0.05. So H1 was accepted and H0 was rejected so that the use of Jigsaw model with audio visual media in the experimental class significantly affected the increase in students’ study results rather than conventional learning. Keywords: Learning Outcomes, Audio Visual Media, Learning Types Jigsaw.